Experimental and analytical research on the hysteretic behavior of steel plate deep beams infill steel frame. (December 2016) - Xu, Yinglu; Zheng, Hong; Ma, Jiangping
Abstract: The aim of this paper is to experimentally and analytically evaluate the hysteretic behavior of steel plate deep beams infill steel frame. Three reduced-scale specimens subjected to cyclic loading have been tested and their responses measured and analyzed. The test results showed the good behavior of the steel plate deep beams infill steel frame, mainly improving the strength, stiffness, ductility and energy dissipation capacity of the steel frame. Then parametric studies, using a finite-element analysis program, were carried out to investigate the structural behavior with variations in: forms of stiffeners, height-width ratio α, height-thickness ratio β, and the size of the column and beam. The numerical results indicate that the parameters of full stiffeners, including cruciform and bilateral stiffeners, α = 0.75, β  = 150 are reasonable for use in steel plate deep beams infill steel frame. Highlights: This paper aims to experimentally and analytically evaluate the hysteretic performance of steel plate deep beams infill steel frame. Three 1:3 scaled steel frames were designed and tested, including one pure steel frame (PF), considered as a benchmark, and two SDBFs with different height-width ratio of steel plate deep beams (SDB). The test results indicate that different strength and stiffness can be obtained through changing the height-width ratio of SDB, thus achieving the objective of controlling the structural stiffness. The SDB do not have much influence on the final failure pattern of the steel frame, however, the steel plate of proper height-width ratio can be used as the main component to resist lateral force, and yield first to dissipate energy. Further, an analytical study was conducted using a nonlinear finite-element program ANSYS to better understand the performance of SDBF. And the parameter recommendation was provided after parametric studies.